Effect of high temperature and relative humidity on host - pest interaction - Hosni, Suzziyana (2017)
Environmental stress such as extreme temperature and relative humidity affect growth and development in plants as well as biotic interactions. In leafy vegetable such as green mustard (Brassica rapa var. parachinensis, ‗sawi hijau‘). High temperature and low relative humidity subjected the vegetable plants vulnerable to grasshopper infestation. Grasshoppers are expected to respond more than other organisms because these are ectoderms. Grasshopper exacerbate the already damage crop due to changes in morphology, biochemistry and physiology in plants caused by extreme abiotic factors. This study aims to understand the mechanisms that are driving the population dynamics of green grasshopper (Caelifera spp.) on green mustard. Specifically, (i) to study the impact of high temperature on plant growth and development; (ii) to observe the insect pest behavior and their habit in high temperature and humid environment; (iii) to determine the host – pest interaction under high temperature and low relative humidity. Insects were introduced in each plant in the simulation chambers in order to observe their relation to plant response under high temperature and low humidity. T-test analyse were used to observe the comparison between interactions of host – pest on two different temperatures. Plant parameters such as transpiration rate, leaf area, plant height, plant development stage, and weight were measured every two days whilst insect pest behavior, feeding habit, development and survival rate were recorded. From the analyses obtained, temperature induces changes in host plant suitability to insect herbivores on account of significant effect on mass of dry matter, plant height and number of leaves. The higher temperature resulting higher pest infestation on vegetable cultivation in various ways. Thus the changes lower the food value, causing insect pest consume more on the plant to meet their nutritional needs.